Heat shock protein 90 modulates cutaneous vasodilation during an exercise‐heat stress, but not during passive whole‐body heating in young women - McGarr, Gregory W. (Physiol Rep, 2020)
Heat shock protein 90 (HSP90) modulates exercise‐induced cutaneous vasodilation in young men via nitric oxide synthase (NOS), but only when core temperature is elevated ~1.0°C. While less is known about modulation of this heat loss response in women during exercise, sex differences may exist. Further, the mechanisms regulating cutaneous vasodilation can differ between exercise‐ and passive‐heat stress. Therefore, in 11 young women (23 ± 3 years), we evaluated whether HSP90 contributes to NOS‐dependent cutaneous vasodilation during exercise (Protocol 1) and passive heating (Protocol 2) and directly compared responses between end‐exercise and a matched core temperature elevation during passive heating. Cutaneous vascular conductance (CVC(%max)) was measured at four forearm skin sites continuously treated with (a) lactated Ringers solution (control), (b) 178 μM Geldanamycin (HSP90 inhibitor), (c) 10 mM L‐NAME (NOS inhibitor), or (d) combined 178 μM Geldanamycin and 10 mM L‐NAME. Participants completed both protocols during the early follicular (low hormone) phase of the menstrual cycle (0–7 days). Protocol 1: participants rested in the heat (35°C) for 70 min and then performed 50 min of moderate‐intensity cycling (~55% VO(2peak)) followed by 30 min of recovery. Protocol 2: participants were passively heated to increase rectal temperature by 1.0°C, comparable to end‐exercise. HSP90 inhibition attenuated CVC(%max) relative to control at end‐exercise (p < .05), but not during passive heating. While NOS inhibition and combined HSP90 + NOS inhibition attenuated CVC(%max) relative to control for both protocols (all p < .05), they did not differ from each other. We show that HSP90 modulates cutaneous vasodilation NOS‐dependently during exercise in young women, with no effect during passive heating, despite a similar NOS contribution.